BENTHIC ALGAL PRODUCTION ACROSS LAKE SIZE GRADIENTS: INTERACTIONS AMONG MORPHOMETRY, NUTRIENTS, AND LIGHT - Yvonne Vadeboncoeur; Garry Peterson; M. Jake Vander Zanden; Jacob Kalff (Ecology, 2008)
Attached algae play a minor role in conceptual and empirical models of lake ecosystem function but paradoxically form the energetic base of food webs that support a wide variety of fishes. To explore the apparent mismatch between perceived limits on contributions of periphyton to whole‐lake primary production and its importance to consumers, we modeled the contribution of periphyton to whole‐ecosystem primary production across lake size, shape, and nutrient gradients. The distribution of available benthic habitat for periphyton is influenced by the ratio of mean depth to maximum depth (DR = 𝑧^/ z max ). We modeled total phytoplankton production from water‐column nutrient availability, 𝑧^, and light. Periphyton production was a function of light‐saturated photosynthesis (BP max ) and light availability at depth. The model demonstrated that depth ratio (DR) and light attenuation strongly determined the maximum possible contribution of benthic algae to lake production, and the benthic proportion of whole‐lake primary production (BP f ) declined with increasing nutrients. Shallow lakes (𝑧^ ≤ 5 m) were insensitive to DR and were dominated by either benthic or pelagic primary productivity depending on trophic status. Moderately deep oligotrophic lakes had substantial contributions by benthic primary productivity at low depth ratios and when maximum benthic photosynthesis was moderate or high. Extremely large, deep lakes always had low fractional contributions of benthic primary production. An analysis of the world's largest lakes showed that the shapes of natural lakes shift increasingly toward lower depth ratios with increasing depth, maximizing the potential importance of littoral primary production in large‐lake food webs. The repeatedly demonstrated importance of periphyton to lake food webs may reflect the combination of low depth ratios and high light penetration characteristic of large, oligotrophic lakes that in turn lead to substantial contributions of periphyton to autochthonous production.

Fluorescent dissolved organic matter in lakes: Relationships with heterotrophicmetabolism - W. K. Levi Cammack; Jacob Kalff; Yves T. Prairie; Erik M. Smith (Limnology and Oceanography, 2004)
Characterizing dissolved organic matter (DOM) composition remains a major unresolved problem in aquatic ecology and is one of the key impediments to developing a good understanding of DOM production and consumption by heterotrophic bacteria. Fluorescence spectroscopy has been proposed as a promising method for characterizing DOM, but few links have been demonstrated between DOM fluorescence and DOM composition or the processes affected by DOM composition. In 28 southern QueÂbec lakes, tryptophan‐like DOM fluorescence (TFDOM) was found to be a much better descriptor of rates of heterotrophic bacterial metabolism than dissolved organic carbon, describing 52%, 44%, 51%, and 55% of the variability in bacterial production, bacterioplankton respiration, total bacterial carbon consumption, and total plankton community respiration, respectively. In addition, evidence from a series of bacterial regrowth cultures suggests that T‐FDOM represents a product of bacterial activity as well as, to a lesser extent, a bioavailable substrate. Our results instead raise the intriguing possibility that TFDOM concentration reflects a balance between its production and consumption by bacteria. We demonstrate here that fluorescence spectroscopy can be used to identify a highly dynamic fraction of DOM related to bacterial metabolism in lakes.

Submerged Macrophyte-bed Effects on Water-Column Phosphorus, Chlorophyll a , and Bacterial Production - Jacob Kalff; Neil Rooney (Ecosystems, 2003)

The role of submerged macrophyte beds in phosphorus and sediment accumulation in Lake Memphremagog, Quebec, Canada - Neil Rooney; Jacob Kalff; Catherine Habel (Limnology and Oceanography, 2003)
The relationships between long‐term (~115‐year) phosphorus and sediment accumulation and submerged macrophyte biomass were determined both within a submerged macrophyte bed and among beds in Lake Memphremagog, Quebec, Canada. Strong relationships between present submerged macrophyte biomass and littoral‐zone sediment and phosphorus accumulation rates both within and among macrophyte beds yielded simple models for estimating long‐term littoral‐zone accumulation rates. Mean sediment particle size at the depth of maximum submerged macrophyte biomass, estimated from water content, was comparable with the mean particle size in profundal zone of Lake Memphremagog, suggesting that energy environments differ little between vegetated littoral zones and profundal zones. The mean total sediment‐accumulation rate of 1.2 mm yr −1 in the macrophyte beds was indistinguishable from average profundal rates of sediment accumulation in North American lakes. Although dense beds accumulated twice as much bulk sediment per unit area (g m −2 yr −1 ) compared with their profundal counterparts, phosphorus accumulation per unit bulk sediment in macrophyte beds with a biomass of 1,000 g m −2 (wet weight) was one sixth that measured in profundal sediments, pointing to large postdepositional losses of sedimented phosphorus (>70%) from macrophyte beds. Finally, extrapolation of the present results to five nearby lakes suggests, based on still‐limited data, that, in lakes in which half of the sediment surface is colonized by submerged macrophytes, the littoral zone accounts for roughly one third of whole‐lake phosphorus and two thirds of whole‐lake bulk sediment accumulated annually.

Interactions among epilimnetic phosphorus, phytoplankton biomass and bacterioplankton metabolism in lakes of varying submerged macrophyte cover - Neil Rooney; Jacob Kalff (Hydrobiologia, 2003)

Volumetric and aerial rates of heterotrophic bacterial production in epi- and hypolimnia: the role of nutrients and system morphometry - André C. P. Cimbleris; Jacob Kalff (Hydrobiologia, 2003)

The contribution of picophytoplankton in marine and freshwater systems of different trophic status and depth - Thomas Bell; Jacob Kalff (Limnology and Oceanography, 2001)
Although there are a number of single system and regional studies on the importance of picophytoplankton (PP; 0.2–2 µm), there has been little effort to quantify their importance on a larger scale and to integrate marine and freshwater studies. We developed empirical models from data in the literature to assess the absolute and relative importance of PP in marine and freshwater. The PP biomass (chlorophyll a [Chl a]) increases with trophic status, here represented by the total Chl a, in both marine and freshwater systems. In addition, PP abundance in freshwater, and primary production in marine waters, increases with trophic status. Even so, the relative importance of the PP biomass and primary production declines systematically with increasing trophic status in both marine and freshwater systems. Both the absolute biomass of PP and the relative contribution of PP biomass to the total phytoplankton community biomass are larger in freshwater at any particular value of total Chl a. In eutrophic lakes, which are typically shallow and particularly susceptible to the greatest phytoplankton resuspension and sediment recruitment, the on average small relative contribution of PP biomass appears affected by a relatively high but variable contribution of resuspended microplankton.

Sediment accumulation and Pb burdens in submerged macrophyte beds - Glenn A. Benoy; Jacob Kalff (Limnology and Oceanography, 1999)
This study quantifies the role of lake morphometry and submerged macrophyte beds on the accumulation of sediments in the littoral zone. Stable Pb, a historical marker of lacustrine sediments in southern Quebec, was used to date the sediments (∼110 yr) and to calculate three long‐term sediment accumulation rates (SARs) in Lake Memphremagog (located in Quebec and Vermont). The anthropogenic Pb burden in the littoral zone of Lake Memphremagog was found to be two to eight times greater (per m 2 ) than the Pb burdens in the profundal zone of surrounding eastern township lakes. Pb concentrations were nearly fourfold higher than background Pb concentrations (115 and 31 μg g −1 , respectively), providing a reliable marker for littoral sediment core analysis. Lake morphometry is related to the three accumulation rates measured by providing distinct threshold limits (i.e., littoral slope, >10% exposure, >10 km 2 ) where sediments are unable to accumulate. Macrophyte beds are shown to disproportionately accumulate sediments at rates 2 to 20 times greater (per m 2 ) than in the profundal zone. Linear regression models show that both the total SAR (mean, 1.7 mm yr −1 ) and organic SAR (mean, 83.1 g m −2 yr −1 ) are best predicted by the biomass density of the macrophytes, closely followed by plant mean biomass. Bulk SAR, principally representing the larger, inorganic fraction of sediments, is least predictable. Biomass density, but not mean biomass, was related to the accumulation rate of stable Pb (mean, 37.7 mg m −2 yr −1 ), supporting empirical models that show growth form to be an important determinant of both sediment and plant tissue elemental concen‐trations. The variety of macrophyte communities sampled across Lake Memphremagog demonstrates that the conclusions drawn are not restricted to monospecific stands but to assemblages as a whole.

Planktonic bacterial respiration as a function of C:N:P ratios across temperate lakes - André C. P. Cimbleris; Jacob Kalff (Hydrobiologia, 1998)

Organic matter mineralization rates in sediments: A within‐ and among‐lake study - Cornelia den Heyer; Jacob Kalff (Limnology and Oceanography, 1998)
Organic matter mineralization rates were measured by the accumulation of DIC + CH 4 in the water overlying intact cores taken from littoral and protimdal sediments of nine Quebec lakes. The variability in areal carbon mineralization is much greater within lakes than among lakes varying in trophic richness. Organic matter mineralization in littoral sediments is more variable and, on average, threefold higher than in the profundal sediments. Sixty percent of the variation in mean summer mineralization rates is explained by site depth, a surrogate variable that incorporates the effect of temperature and may also be reflecting substrate quality and(or) supply. The lakes‐pecific characteristics most strongly correlated to the residuals of the regression with depth are catchment area‐to‐lake area ratio (CA:LA) and water residence time. In lakes with a larger CA:LA and a shorter residence time, the amount and(or) the quality of organic matter settling to the sediments at a given depth may be reduced, resulting in the lower observed mineralization rates. Total mineralization in the sediments is, not surprisingly, greater in larger lakes but the rate per unit area is smaller, reflecting the decreased importance of the littoral zone. More than half (54–100%) of the DIC + CH 4 produced in the sediments is from the littoral zone. Yet, because of the large biomass in epilinmetic waters, the littoral sediments account for